Pregnancy Outcomes of Exacerbated Chronic Hypertension Compared with Superimposed Preeclampsia - Becker, David A.; Machemehl, Hannah C.; Biggio, Joseph R.; Siegel, Anne M.; Tita, Alan T.; Harper, Lorie M. (American Journal of Perinatology, 2019)
Objective Compare outcomes in women with chronic hypertension who remain normotensive, experience exacerbation, or meet laboratory criteria for superimposed preeclampsia.Study Design This is a retrospective cohort study of singleton pregnancies with chronic hypertension from 2000 to 2014. Delivery admission records were used to categorize women into three groups: stable chronic hypertension, exacerbated hypertension, and superimposed preeclampsia. The primary outcomes were a neonatal composite of death, respiratory support, umbilical arterial pH < 7, 5-minute Apgar ≤3, and seizures, in addition to maternal severe hypertension requiring intravenous (IV) antihypertensives.Results In total, 270 women (31.3%) had stable hypertension, 429 (49.8%) had exacerbated hypertension, and 163 (18.9%) had superimposed preeclampsia. Neonatal composite (10.7 vs. 11.2 vs. 21.5%; p < 0.01) and preterm birth <35 weeks (8.8 vs. 18.3 vs. 35.7%; p < 0.01) were highest in the superimposed preeclampsia group. Severe hypertension requiring the use of IV antihypertensives increased across groups (0 vs. 15.6 vs. 23.3% p < 0.01). With the exception of severe hypertension requiring IV antihypertensive use, outcomes in women with exacerbations were unchanged compared with those with stable hypertension.Conclusion Superimposed preeclampsia is associated with an increased risk of adverse neonatal outcomes compared with stable chronic hypertension, whereas exacerbation of chronic hypertension is not.
Keywords: chronic hypertension; preeclampsia; hypertension exacerbation; neonatal morbidity; maternal morbidity